MELESTARIKAN MINUMAN TRADISIONAL: PELATIHAN PEMBUATAN BIR PLETOK DI DESA SAMIREJO - Nova Oktaviana; Rike SeptiAnanta; Novita Dwi Setyaningrum; Sherly Kristina Murti; Desy Larasati; Umi Faridah; Septiani; Adelia Putri Widyani; Annisa Ramadhani; Anisya Maulida Zulfa; Rika Kusmawati; Erli Khaizatun Az-Zahra; Mohammad Faruq Fathurrahman; Farza Attaya Ma`arij; Yunita Dwi Kusuma Wardani; Arif Rohman Hakim; Nafi`ah Khumairatun Az-Zahra; Vila Saputri; Fitri Ayu Kusumawati; Achmad Saiq (Nusadaya Journal of Multidiciplinary Studies, 2026)
Bir pletok herbal medicine is a traditional drink that has not been widely developed in the Samirejo area, even though it has great potential as an herbal drink that uses spices that are good for health. The lack of public understanding about the benefits and how to make bir pletok herbal medicine is one of the reasons why this traditional drink is not widely used. This community service activity aims to find out how the people of Samirejo Village view jamu bir pletok after consuming it and after receiving an explanation of its benefits and how to make it. The method used is descriptive quantitative, using structured interviews with 50 respondents selected using purposive sampling techniques. The variables measured included perceptions of taste, health benefits, effects after drinking, and interest in consuming it again. Data analysis was performed descriptively, using means, medians, and percentages. The results showed that the community had a positive view of bir pletok herbal medicine, liked its taste, felt the health benefits it provided, and were very interested in buying it again. The education provided helped the community understand how to process and utilize bir pletok herbal medicine as a local traditional herbal drink with further development potential.